Effect on 3D-printability and microstructure of pork paste partially replaced with yellow mealworm larvae paste - Jinbo Xu; Jiaqi Liu; Hui Wang; Qian Liu; Qian Chen; Fangda Sun; Baohua Kong (Future Foods)
Yellow mealworm larvae (Tenebrio molitor L.) (YML) are a readily available source of non-conventional protein with high nutritional value and feed conversion efficiency. However, they remain unaccepted by most consumers. This study examines the feasibility of substituting pork paste with YML paste (YMLP) at graded substitution levels (0–75 %), while concurrently evaluating the resultant effects on both nutritional composition and 3D-printing performance parameters in pork-YML composite matrices. Proximate composition analysis showed that YML substitution elevated ash content while maintaining baseline protein levels in the composite matrices, concurrently enhancing the overall nutritional profile of the experimental samples. The mixed pastes’ 3D printability was determined by measuring their rheological and microstructural properties. The Fourier-transform infrared spectroscopy results showed that the addition of YML increased the content of chitin, and the disentanglement and reorientation of chitin resulted in a decrease in viscosity and an increase in shear-thinning behavior which are shown in the rheological results. The texture profile analysis showed that the hardness, resilience, cohesiveness, and chewiness of the steamed 3D-printed samples were reduced with an increase in the YMLP replacement ratio (P < 0.05), which was due to the destruction of the 3D gel network as shown in scanning electron microscopy. Overall, while increasing the YMLP replacement ratio reduced the self-supporting capacity of printed samples and disrupted the 3D gel network structure, consequently diminishing printability and textural properties, successful substitution was achieved at a 30 % ratio. This optimal substitution level maintained functional performance while enhancing the nutritional profile of the pork-based matrices.